2020
DOI: 10.3389/fphar.2020.01337
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of the Efficacy of Sinitang Decoction Against Ulcerative Colitis

Abstract: The aim of this study was to investigate the precise clinical use of Sinitang decoction (SNT) in ulcerative colitis (UC). Network pharmacology-based analysis of the drug components–targets–diseases–pathways was used to predict the possible clinical applications of SNT. Next, 2,4,6-trinitrobenzenesulfonic acid (TNBS) was used to establish a rat model of UC, and the efficacy of SNT against UC was tested, followed by a proteomic analysis of the specific signatures regulated by SNT against UC. SNT was predicted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The expression of OLFM4 was highly upregulated in inflamed colonic epithelium, especially in UC ( Gersemann et al, 2012 ; Suzuki et al, 2018 ). Furthermore, the relationships between IBD and some of the top DEGs ( Figure 2B ), such as MMP1 ( Wang and Qiu, 2010 ) and COL12A1 ( Ji et al, 2020 ), have also been reported. Interestingly, the serum levels of LOXL2 are significantly higher in primary sclerosing cholangitis (PSC) ( Pollheimer et al, 2018 ), which is closely associated with IBD, and LOXL2 targeting in IBD has been evaluated in PSC ( Lynch et al, 2019 ).…”
Section: Resultsmentioning
confidence: 81%
“…The expression of OLFM4 was highly upregulated in inflamed colonic epithelium, especially in UC ( Gersemann et al, 2012 ; Suzuki et al, 2018 ). Furthermore, the relationships between IBD and some of the top DEGs ( Figure 2B ), such as MMP1 ( Wang and Qiu, 2010 ) and COL12A1 ( Ji et al, 2020 ), have also been reported. Interestingly, the serum levels of LOXL2 are significantly higher in primary sclerosing cholangitis (PSC) ( Pollheimer et al, 2018 ), which is closely associated with IBD, and LOXL2 targeting in IBD has been evaluated in PSC ( Lynch et al, 2019 ).…”
Section: Resultsmentioning
confidence: 81%
“…The harvested distal colons of each experimental group were sliced, and the pathological evaluation of the colon lesions of the mice in each group was performed. A 0.5 cm piece of colon tissue was embedded in paraffin after being treated in 4% paraformaldehyde for 48 h. Hematoxylin and Eosin (H&E) was used to stain 5 µm–thick sections [ 19 ]. Colon tissue damage was observed under light microscopy at different magnifications, and histopathological scoring was performed based on seven aspects [ 17 ]: Degree of inflammation (score ranged from 0~4 for Normal, Mucosal, Submucosal, Muscular and Serous involvement), Degree of damage to the crypt (score ranged from 0~4 for Normal, basal 1/3 of the crypt, basal 2/3 of the crypt, entire crypt involvement and damage to the crypt and ulceration), Crypt abscesses (score ranged from 0~2 for Normal, Unifocal and Multifocal involvement), Infiltration of inflammatory cells, Degree of submucosal edema, Goblet cell reduction, Degree of epithelial hyperplasia (score ranged from 0~3 for Normal, Unifocal, Multifocal and Diffuse involvement).…”
Section: Methodsmentioning
confidence: 99%
“…After the experiment, the fecal broth was centrifuged at 10,000 r/min for 10 min at 4 °C; the supernatant was extracted, mixed with the internal standard crotonic acid at a ratio of 5:1, and refrigerated and acidified for more than 24 h. Finally, it was used for gas chromatography to measure the amounts of acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid and isovaleric acid in fecal bacteria fermentation acidification solution [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each group consisted of six rats. Except the normal group, all groups were administered with a single TNBS enema to induce acute colitis (100 mg/kg) ( Ji et al, 2020 ), 8 cm from the anus, using a catheter. The normal group was administered the same amount of vehicle (paroline) enema as the control.…”
Section: Methodsmentioning
confidence: 99%